Materiais corretivos e nitrogênio na nutričão e na produčão de matéria seca de cana-de-ačúcar cultivada em vaso - Da Gama Basto, Joani Cristina Hungaro Aires [UNESP]; Cazetta, Jairo Osvaldo [UNESP]; De Mello Prado, Renato [UNESP] (My University, 2010)
Silicon is a beneficial element that can increase the yield of sugarcane, especially when associated with nitrogen. The aim of this study was to evaluate the effects of silicate slag as a source of Si and its interaction with soil N on nutrition and dry matter production of sugar cane. The treatments consisted of two sources of correctives (limestone and silicate slag) in three doses (one half, once and twice the dose shown to increase V to 60%), two N rates (300 e 600mg·dm-3) administered as urea, a control (without corrective and without N), arranged in a completely randomized factorial design 2×3×2+1, with four replicates. Each experimental unit was constituted by a 40dm3 pot filled with an Oxisol (V= 10% and Si= 10.3mg·dm-3), and 4 seedlings (SP79-1011). The nutritional status (Si and N) was evaluated 10 months after planting the sugarcane, as well as the Si content of the soil and shoot dry matter. The application of silicate slag increased the content of available Si in soil and the plant. The application of corrective materials improved the nutrition and dry matter production of sugarcane. Nitrogen fertilization was not significant for dry matter production of the sugarcane-plant, regardless of the source of corrective material.
Corrective materials and nitrogen in nutrition and dry Matter production of sugarcane cultivated in pots